2017
DOI: 10.2172/1343365
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Low-Molecular Weight Polydimethylsiloxane Fluids

Abstract: Physical property measurements including viscosity, density, thermal conductivity, and heat capacity of low-molecular weight polydimethylsiloxane (PDMS) fluids were measured over a wide temperature range (˗50 o C to 150 o C when possible). Properties of blends of 1 cSt and 20 cSt PDMS fluids were also investigated. Uncertainties in the measurements are cited. These measurements will provide greater fidelity predictions of environmental sensing device behavior in hot and cold environments. NOMENCLATURE CO 2 Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…A12728, CAS 63148‐62‐9, $200/L, MW: 3784 g/mol, density: 0.96 g/cm 3 , viscosity: 52.4 mm 2 /s @ 25°C, Supplier: Fisher Scientific, Hampton, NH), and glycerol (Fisher Scientific, Stock No. S25342B, CAS 56‐81‐5, $23/L, MW: 92 g/mol, density: 1.25 g/cm 3 , Supplier: Fisher Scientific) . T 1 and T 2 were compared to the ACR large phantom electrolyte liquid (10 mM NiCl 2 and 75 mM NaCl in water) and deionized water measured values .…”
Section: Methodsmentioning
confidence: 99%
“…A12728, CAS 63148‐62‐9, $200/L, MW: 3784 g/mol, density: 0.96 g/cm 3 , viscosity: 52.4 mm 2 /s @ 25°C, Supplier: Fisher Scientific, Hampton, NH), and glycerol (Fisher Scientific, Stock No. S25342B, CAS 56‐81‐5, $23/L, MW: 92 g/mol, density: 1.25 g/cm 3 , Supplier: Fisher Scientific) . T 1 and T 2 were compared to the ACR large phantom electrolyte liquid (10 mM NiCl 2 and 75 mM NaCl in water) and deionized water measured values .…”
Section: Methodsmentioning
confidence: 99%
“…Further, decreasing the gel fraction was expected to lower the density of the membranes through the formation of more voids in the crosslinked structure, but it tended to increase with a decrease in gel fraction values ( Table 1 ). This is attributed to the reduced content of highly flexible PDMS units, which are known to be low-density [ 39 ]. Moreover, it was found that the poly(NB-Ad) had a higher density value than x(PEG/PPG: PDMS:Ad)s, strongly suggesting that the density of our crosslinked membranes is highly dependent on the density of each component used.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the schematic in Figure 10a shows intercalated octanoic acid molecules within the silicone oil (polydimethylsiloxane, PDMS) matrix, hindering the flow of polymer molecules past each other. (Note that the molecular weight of PDMS comprising the 20 cSt silicone oil (≈2000 g/mol [53]) used in this study is well below the molecular weight at which chain entanglement is first observed, ≈27,500 [68]). behavior is an indication of molecular structuring in the binary mixtures, with the mole ratio of ≈0.67 again indicating the optimum packing of the components to achieve the greatest change in viscosity.…”
Section: Evidence Of Molecular Interactions From Mixture Viscositymentioning
confidence: 89%
“…It is important to note that the electrical conductivity of 1-octanol is around four to five orders of magnitude greater than the other liquids. The dynamic viscosity is highest for silicone oil, which comprises approximately 30 dimethylsiloxane (DMS) repeat units, i.e., H 3 C-[Si(CH 3 ) 2 -O] n -CH 3 , with a molecular weight of ≈2000 [53]. The surface tensions of the liquids are all similar, the relatively low values indicating that the liquids are dominated by dispersion interactions; the slightly higher surface tension for 1-octanol indicates a relatively small degree of polar (including hydrogen bonding) character (also consistent with its dielectric constant value of ≈10 and dipole moment ≈1.7 D in dilute solution [16].…”
Section: Properties Of the Liquidsmentioning
confidence: 99%